Citrus Waste as Source of Bioactive Compounds: Extraction and Utilization in Health and Food Industry - Zahra Maqbool; Waseem Khalid; Hafiz Taimoor Atiq; Hyrije Koraqi; Zaryab Javaid; Sadeq K. Alhag; Laila A. Al-Shuraym; D. M. D. Bader; Mohammed Almarzuq; Mohamed Afifi; Ammar AL-Farga (Molecules, 2023)
The current research was conducted to extract the bioactive compounds from citrus waste and assess their role in the development of functional foods to treat different disorders. The scientific name of citrus is Citrus L. and it belongs to the Rutaceae family. It is one of the most important fruit crops that is grown throughout the world. During processing, a large amount of waste is produced from citrus fruits in the form of peel, seeds, and pomace. Every year, the citrus processing industry creates a large amount of waste. The citrus waste is composed of highly bioactive substances and phytochemicals, including essential oils (EOs), ascorbic acid, sugars, carotenoids, flavonoids, dietary fiber, polyphenols, and a range of trace elements. These valuable compounds are used to develop functional foods, including baked products, beverages, meat products, and dairy products. Moreover, these functional foods play an important role in treating various disorders, including anti-aging, anti-mutagenic, antidiabetic, anti-carcinogenic, anti-allergenic, anti-oxidative, anti-inflammatory, neuroprotective, and cardiovascular-protective activity. EOs are complex and contain several naturally occurring bioactive compounds that are frequently used as the best substitutes in the food industry. Citrus essential oils have many uses in the packaging and food safety industries. They can also be used as an alternative preservative to extend the shelf lives of different food products.